Ulcerative Colitis Etiology, Diagnosis, Diet, Special Populations, and the Role of Interventional Endoscopy - Pal, Partha (IntechOpen, 2022)
Ulcerative colitis (UC) is one of the major forms of inflammatory bowel disease (IBD). Epidemiological trends suggest an initial rise in the incidence of UC, followed by Crohn's disease (CD), in areas where IBD is emerging. As understanding of aspects of the disease is evolving, this book covers new perspectives on the etiology, clinical manifestations, diagnosis, and management of UC. Genetic predisposition, along with gut dysbiosis and environmental factors, triggers the altered gut permeability and dysregulated immune activation that leads to the development of UC, which can manifest both intestinally and extra-intestinally. Platelets play a significant role in augmenting inflammation. Histological examination is important for accurate diagnosis and for distinguishing mimics. Histological remission is an emerging treatment target strategy in UC. Novel treatments include dietary manipulation with anti-inflammatory dietary components like fermented rice bran. A number of challenges need to be addressed in treating special populations like children and pregnant women. Finally, interventional endoscopy is playing an emerging role in the management of colitis-associated neoplasia and postoperative complications and acting as a bridge between surgery and medical therapy. Ulcerative Colitis - Etiology, Diagnosis, Diet, Special Populations, and the Role of Interventional Endoscopy aims to act as a ready reference for the clinician. It provides indispensable updates on several relevant issues in the diagnosis and management of ulcerative colitis and has benefited from the collaboration of leading experts in various aspects of the disease. It aims to facilitate decision-making by gastroenterologists, IBD specialists, interventional endoscopists, dieticians, pathologists, surgeons, and pediatricians treating UC patients.